Magnetotransport properties of microstructured AlCu2Mn Heusler alloy thin films in the amorphous and crystalline phase - Barzola-Quiquia J. (2018)
We have studied the resistance, magnetoresistance and Hall effect of AlCu2Mn Heusler alloy thin films prepared by flash evaporation on substrates cooled at 4He liquid temperature. The as-prepared samples were amorphous and were annealed stepwise to induce the transformation to the crystalline phase. The amorphous phase is metastable up to above room temperature and the transition to the crystalline phase was observed by means of resistance measurements.